THE INFLUENCE OF KNOWLEDGE AND MOTIVATION ON BREASTFEEDING BEHAVIOR IN MOTHERS: A PATH ANALYSIS - Septiana Juwita; Sri Anggarini Parwatiningsih (Jurnal Kebidanan Indonesia, 2026)
Exclusive breastfeeding during the first six months of life is a global recommendation that has been proven to provide optimal benefits for infant health and development. However, the coverage rate of exclusive breastfeeding in Indonesia has not yet met the national target. This study aims to analyze the influence of knowledge and motivation on maternal breastfeeding behavior, both directly and indirectly, using a path analysis approach.This research employed a quantitative cross-sectional design involving 129 breastfeeding mothers within the working area of the Surakarta Health Office. Data were collected through a questionnaire and analyzed using the AMOS program.The findings revealed that knowledge significantly influenced motivation (β = 0.873) and breastfeeding behavior (β = 0.765), while motivation also had a significant effect on behavior (β = 0.249). The total effect of knowledge on breastfeeding behavior was β = 0.983, including an indirect effect through motivation amounting to 0.218.These findings highlight that knowledge is the dominant factor in shaping breastfeeding behavior, with motivation acting as a partial mediator. Integrated educational and motivational interventions are therefore necessary to enhance the success of exclusive breastfeeding.